Fluctuations in running and skill-related performance in elite rugby union match-play - Lacome, M.; Piscione, J.; Hager, J.-P.; Carling, C. (European Journal of Sport Science, 2017)
This study investigated end-game and transient changes in running activities and whether these were concomitantly associated with reductions in skill-related performance in senior international rugby union match-play. Altogether, 18 official matches were analysed (322 individual observations) using computerised video-based tracking and event coding (Amisco Pro®, SUP, Nice, France). In forwards and backs, trivial to small reductions (% difference: -2.1, ±1.3 to -10.0, ±4.0%) in total distance and that covered at high speeds (>18.0 km h-1) occurred in the second- versus the first-half while there were trivial differences in skill-related performance measures (-2.3, ±4.5 to 7.5, ±14.0%). In both positions, small to moderate declines (-42, ±10 to -21, ±7%) occurred in high-speed running in the final 10-min and 5-min periods versus mean values for all other 10-min and 5-min periods throughout the game while only small changes (-18, ±51 to 13, ±41%) in skill-related performance were observed. Trivial changes in running and skill-related performance (-11, ±74 to 7, ±39%) were observed in the 5-min period immediately following the most intense 5-minute periods of play compared to mean performance over the other 5-min periods. These findings suggest that international rugby union players were generally able to maintain skill-related performance over the course of match-play even when declines in running performance occurred.